Opioid Mortality Following Implementation of Medical Cannabis Programs in the United States - Kaufman, Daniel E.; Nihal, Asawer M.; Leppo, Janan D.; Staples, Kelly M.; McCall, Kenneth L.; Piper, Brian J. (Pharmacopsychiatry, 2021)
Introduction The United States is in the midst of an opioid overdose epidemic. Emerging evidence suggests that medical cannabis (MC) may reduce use of opioids for pain in some individuals, with potential impacts on opioid-related overdose. However, there may be other important differences between states that did, and did not, adopt MC.Methods This study evaluated differences following legal MC sales on US opioid-related overdose deaths, corrected for population, from 1999 to 2017 using an interrupted time series. Comparisons by MC status were also made for Medicaid expansion and the Centers for Disease Control death certificate reporting quality (0: <good, 1: good, 2: excellent).Results Overdose deaths were significantly higher in MC states from 2012–2017. Overdose death slopes over time increased in states with (pre=1.46±0.46, post=2.90±0.58, p<0.05) and without (pre =0.20±.10, post=1.04±0.22, p<0.005) MC. Post-legalization slopes were significantly higher in MC states (p<0.01). Two states without (11.1%) as compared to 11 states with (91.7%) MC expanded Medicaid by 2014 (χ2[1]=19.03, p<0.0005). MC states (1.50±0.23) had higher death certificate reporting quality relative to states without MC (0.78±0.22, p<0.05).Discussion MC states had higher rates of opioid overdoses. Although there was no decrease in association with MC introduction, these results were confounded by states without MC having lower overdose reporting quality. Medicaid expansion was also more common in states with MC. Finally, the potency of fentanyl analogues may have obscured any protective effects of MC against illicit opioid harms.